Competitive adsorption behavior of β-lactoglobulin, α-lactalbumin, bovin serum albumin in presence of hydroxypropylmethylcellulose: influence of pH - Jara, Federico Luis (2013)
The interfacial properties at the air–water (A/W) of each individual whey proteins (β-lactoglobulin, β-lg; α-lactalbumin, α-la; bovin serum albumin, BSA), and their mixtures with a surface-active polysaccharide, hydroxypropylmethylcellulose (HPMC) were studied at pH 3 or 6. The interfacial films were studied by measurement surface pressure (π) isotherms and dynamics of adsorption. At equilibrium proteins surface activity was affected by pH only at low concentrations (below 1·10−2 % wt/wt), due to their pH-dependent conformational changes. HPMC resulted less surface active at pH 3 (below 1·10−4 % wt/wt concentration) that at pH 6. On kinetic studies (π–t), the behavior of β-lg, HPMC and BSA did not change with pH but α-la presented a higher surface activity at pH 3 than 6, even on saturating bulk concentrations. Mixtures of β-lg or BSA with HPMC showed a behavior in between that of single components revealing a net competence for the interface but the mixture α-la and HPMC at pH 6 showed an enhance adsorption. Rheological studies (surface dilatational elastic, Ed, over time) presented the major differences for pHs evaluated. The α-la formed extremely viscoelastic films at pH 6.0, while at pH 3 has the lowest Ed value. β-lg and HPMC films were more viscoelastic at pH 6, being Ed protein film higher. Finally, BSA presented the lowest viscoelastic films without differences between both pHs. For mixtures: i) at pH 6 β-lg/HPMC mixture Ed was dominated by HPMC; at pH 3.0, Ed begins dominated by HPMC, reaching an intermediate value; ii) α-la/HPMC mixture formed more viscoelastic films at pH 6.0 with an intermediate Ed value, while at pH 3.0 the Ed is dominated by protein; iii) BSA/HPMC mixture presented a similar trend in Ed behavior at both pHs.